2021
DOI: 10.1029/2021pa004223
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene Precipitation Fluctuations in South America Triggered by Variability of the North Atlantic Overturning Circulation

Abstract:  Marine record documents decadal-to millennial-scale fluctuations of monsoonal rainfall in eastern South America during the past 5000 years  Precipitation variability was caused by antiphased shifts of the South Atlantic Convergence Zone and South American Low-Level Jet  Changes in oceanic overturning strength mediate transfer of high-northern-latitude climate disturbances into Southern Hemisphere tropics Accepted ArticleThis article has been accepted for publication and undergone full peer review but has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Moreover, our data show reduced summer monsoon precipitation during MIS 6. A driver of reduced summer precipitation in the Doce Basin could be a weakened SACZ caused by reduced AMOC during MIS 6, leading to higher temperatures at the SW Atlantic and shifting the sea-land interaction and thus the strength of the convection belts, as previously described for eastern Brazil during reduced AMOC phases of the Holocene (Bahr et al, 2021).…”
Section: High Northern Latitude Temperatures and Local Precipitationmentioning
confidence: 77%
See 1 more Smart Citation
“…Moreover, our data show reduced summer monsoon precipitation during MIS 6. A driver of reduced summer precipitation in the Doce Basin could be a weakened SACZ caused by reduced AMOC during MIS 6, leading to higher temperatures at the SW Atlantic and shifting the sea-land interaction and thus the strength of the convection belts, as previously described for eastern Brazil during reduced AMOC phases of the Holocene (Bahr et al, 2021).…”
Section: High Northern Latitude Temperatures and Local Precipitationmentioning
confidence: 77%
“…Paleoclimate studies from the last glacial period and the Holocene indicate that solar irradiation and high latitude temperature changes affect South American monsoonal precipitation patterns by impacting atmospheric as well as ocean circulation and SST distribution in the tropical South Atlantic (e.g., Bahr et al, 2021;Cruz et al, 2009Cruz et al, , 2005Jaeschke et al, 2007;Kanner et al, 2012;Stríkis et al, 2018Stríkis et al, , 2015. In eastern Brazil, monsoon intensity over the past 300 ka was primarily controlled by precession-forced changes in insolation but also indirectly affected by changing atmospheric greenhouse gas concentrations, which can modify both the interand intrahemispheric temperature gradients (Rind, 1998;Hou et al, 2020a) and thereby intensity of the Hadley circulation and southeast trade winds (Seo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Al, Si, K, Fe, Ti) and Ca, reflecting marine biogenic carbonate. In addition, we utilize ln(K/Al) and ln(Al/Si) ratios, which have been used to infer changes in continental moisture availability favoring chemical weathering in monsoonal dominated realms (Chiessi et al, 2010;Govin et al, 2012;Clift et al, 2014;Croudace and Rothwell, 2015;Bahr et al, 2021). Here, ln(K/Al) represents a measure of the intensification of chemical weathering as K is indicative for minerals (i.e.…”
Section: Bulk Sediment Elemental Analysismentioning
confidence: 99%
“…Modern clay mineral compositions along the eastern and southeastern South American continental shelf clearly reflect the weathering regime of the hinterland as kaolinite is predominant in the southeast and illite increase northward as more arid conditions prevail in ESA (Tintelnot, 1995). Thus, downcore ln(K/Al) of Core M125-35-2 is a pertinent proxy reflecting changes in the clay mineral composition which is strongly dependent on hinterland chemical weathering intensity and hence, moisture availability (Bahr et al, 2021). As related to past hydroclimate, low (high) ln(K/Al) reflect wetter (drier) conditions within the catchment area.…”
Section: Bulk Sediment Elemental Analysismentioning
confidence: 99%
“…Previous studies have shown that the Roman Warm Period (300-1 CE), Dark Ages Cold Period (800-300 CE), Medieval Climate Anomaly (1300-800 CE), and Little Ice Age (1900-1300 CE) [16,46,55] were associated with oscillations in orbital dynamics, the release of sulfates during volcanic eruptions, an increase in CO 2 concentrations in the atmosphere, and a displacement of the Intertropical Convergence Zone (ITCZ) [15,46,56]. Furthermore, the colder-warmer climate oscillations presented environmental anti-phases between the Northern and Southern Hemispheres during the Late Holocene.…”
Section: Introductionmentioning
confidence: 99%